Multidrug-resistant tuberculosis incidence in the Laayoune Sakia Al-Hamra region, Morocco: Retrospective analysis from 2019 to 2022 - Zegmout, Adil; Zagaouch, Dalal; El-Arbaoui, Maria; Bouida, Abdelfattah; El-Barnoussi, Nadia; Amensour, Mahassine; Lambatten, Dalal (Journal of medical and pharmaceutical sciences, 2024)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) presents a major public health challenge due to its therapeutic complexity and economic impacts.  Materials and Methods: We conducted a descriptive and analytical cross-sectional study at the centre for diagnosis of tuberculosis and respiratory diseases of Laayoune, Morocco, over four years, aiming to describe the epidemiological, clinical, therapeutic, and evolutionary profiles of MDR-TB in the Laayoune Sakia Al Hamra region.  Results: The annual incidence of MDR-TB was lower than the national incidence. Patients were primarily young men between the ages of 20 and 40 living in urban areas. The most frequent symptoms were cough and fever. All patients were diagnosed using molecular biology techniques (Genexpert, Genotype MTBDR plus and Genotype MTBDR sl). The short-course treatment resulted in a cure rate of 62.5%, with a 25% treatment abandonment rate and a 12.5% mortality rate. Risk factors for poor therapeutic response included smoking (p=0.02), weight loss (p=0.02), starting treatment during the COVID-19 period (p=0.02), and treatment abandonment with poor adherence (p=0.03). Conclusion: The results emphasize the need to address risk factors such as smoking and weight loss to improve the management of multidrug-resistant tuberculosis. Short-term treatment is effective for eligible patients. Increasing awareness and implementing targeted interventions are crucial for enhancing treatment adherence and achieving better long-term outcomes.
Keywords: Multidrug-Resistant tuberculosis; epidemiology; prognosis factors; Morocco; Laâyoune Sakia Al Hamra